Analysis Of Hydroquinone Levels In Skin-Lightening Creams Available In Kuala Kurun City, Gunung Mas Regency, Using Uv-Vis Spectrophotometry - Gresty Chintamy; Rahmadani Rahmadani; Salwati Salwati; Nur Hidayah (International Journal of Health Engineering and Technology, 2026)
The growing public interest in skincare products has coincided with an increase in the use of skin-lightening creams. However, hydroquinone an ingredient banned in cosmetics due to its potential to cause side effects such as ochronosis, dermatitis, and other skin disorders is still found in some skin-lightening creams. Therefore, analysis of hydroquinone content is necessary to ensure product safety in accordance with BPOM regulations. To determine the hydroquinone content and concentration of skin-lightening creams available in Kuala Kurun City, Gunung Mas Regency, and to assess whether these levels comply with the limits set by BPOM. This study was an observational analysis using UV-Vis spectrophotometry. Qualitative analysis was measured based on the maximum wavelength of compound absorption to confirm the presence of samples, while quantitative analysis was measured based on light absorption intensity (absorbance) proportional to the concentration of hydroquinone compounds in the samples using a calibration curve. The results of the study of facial whitening creams circulating in Kuala Kurun City, Gunung Mas Regency, found hydroquinone in all five samples, with concentrations of 0.334% in sample A, 0.392% in sample B, sample C at 1.902%, sample D at 1.920%, and sample E at 2.553%. Hydroquinone was detected in all samples of skin-lightening creams, with concentrations ranging from 0.334% to 2.553%. This violates BPOM regulations, as hydroquinone is prohibited in cosmetics and is permitted only at a maximum concentration of 0.02% in artificial nails; therefore, these products do not meet cosmetic safety requirements.